Development of the velocity for vault runs in artistic gymnastics for the last decade - Naundorf, F.; Brehmer, S.; Knoll, Kl.; Bronst, A.; Wagner, R. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The last decade in gymnastics is affected by two revolutionary changes. The introductions of the new vaulting table replacing the former vaulting horse and the 2006 code of points for the evaluation of the competition exercises with an unlimited system removing the maximum value of 10 points are unprecedented large changes in the history of gymnastics. Using competition analysis of the world championships 1997 and 2007 the development on the apparatus vault focused on the running velocity (laser velocity measuring) is described. The main results are: For Yurchenko vaults 2007 women are as fast as men. There has been an important increase in vault run speed since 1997 for men and women. There is one remarkable exception: On Yurchenko vaults men are as fast as ten years before and there is no effect of the new vault table.